(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the relationship between the level of discipline and the achievements of Jambi City judo athletes in 2024. The research method used is a quantitative approach with a correlational design. The research subjects consisted of 20 judo athletes aged 11–25 years who are members of the Jambi City PJSI City Executive Board. Discipline data were collected through a Likert scale questionnaire, while achievement data were obtained from official championship records and coach assessments. The results showed that the level of discipline of judo athletes was in the fairly good category with a percentage of 72.4%, while the level of athlete achievement was also in the fairly good category with a percentage of 75.4%. Data analysis showed a positive relationship between discipline and achievement, where the higher the athlete’s discipline, the better the achievement. Thus, it can be concluded that discipline development, especially in aspects of training consistency, focus, and target achievement, is an important factor in improving the performance of Jambi City judo athletes.